(untitled) (Research, Society and Development, 2020)
This article aims to address the culture of rape that manifests itself in the music charts in Brazil; with this, the conceptualization of machismo was made, soon after the contextualization of the songs in general and, finally, the manifestations of machismo in Brazilian songs were analyzed. This research was carried out through readings and analysis of songs as well as music videos related to the theme studied, based on the theoretical assumption on Critical Discourse Analysis (ADC) supported by Silva Júnior (2017). Thus, we used the bibliographic research of qualitative nature, because it allows, based on Minayo (2008) a better interpretation and reflection of the facts studied. In conclusion, the results showed that the songs bear the marks of a country that to this day lives the marks of patriarchy that brings in its boon the macho culture and establishes the practice of rape as something natural since it can be shown to the public with acceptance of the majority through the musical charts.